Octacalcium phosphate, a promising bone substitute material: a narrative review - Jooseong Kim; Sukyoung Kim; Inhwan Song (Journal of Yeungnam Medical Science, 2024)
Biomaterials have been used to supplement and restore function and structure by replacing or restoring parts of damaged tissues and organs. In ancient times, the medical use of biomaterials was limited owing to infection during surgery and poor surgical techniques. However, in modern times, the medical applications of biomaterials are diversifying owing to great developments in material science and medical technology. In this paper, we introduce biomaterials, focusing on calcium phosphate ceramics, including octacalcium phosphate, which has recently attracted attention as a bone graft material.